The Influence of Social and Economic Factors of Entrepreneurs on SMEs in West Java - Marti’ah, Siti; Theodora, Berta Dian (Universitas Serambi Mekkah, 2021)
The population of entrepreneurs in Indonesia has increased from 1.6% to 3.47%. The number of women who work in the field of entrepreneurship is now 2.4 times more than men although the businesses for women tend to be smaller and grow more slowly than those for men. There are some constraints causing women to be reluctant to practice entrepreneurship, such as limited information, lack of profiles to imitate, limited access to business finance, lack of experience in doing business, and a low level of confidence to start and develop a business. Low level of education and ideological barriers of women related to the household, known as the